VLSI Design for Video Coding H.264/AVC Encoding from Standard Specification to Chip - Lin, Youn-Long Steve. (Springer US, 2010)
Back Cover Copy VLSI Design for Video Coding By: Youn-Long Lin Chao-Yang Kao Jian-Wen Chen Hung-Chih Kuo High definition video requires substantial compression in order to be transmitted or stored economically. Advances in video coding standards from MPEG-1, MPEG-2, MPEG-4 to H.264/AVC have provided ever increasing coding efficiency, at the expense of great computational complexity which can only be delivered through massively parallel processing. This book presents VLSI architectural design and chip implementation for high definition H.264/AVC video encoding with a complete FPGA prototype. It serves as an invaluable reference for anyone interested in VLSI design for video coding. " Presents state-of-the-art VLSI architectural design and chip implementation for high definition H.264/AVC video encoding; " Employs massively parallel processing to deliver 1080pHD, with efficient design that can be prototyped via FPGA; " Every subsystem is presented from standard specification, algorithmic description, design considerations, timing planning, block diagram to test-bench verification;